2000
DOI: 10.1074/jbc.275.6.4127
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Pex5p, the Type 1 Peroxisome Targeting Signal Receptor, with the Peroxisomal Membrane Proteins Pex14p and Pex13p

Abstract: Pex5p, a receptor for peroxisomal matrix proteins with a type 1 peroxisome targeting signal (PTS1), has been proposed to cycle from the cytoplasm to the peroxisomal membrane where it docks with Pex14p and Pex13p, the latter an SH3 domain-containing protein.Using in vitro binding assays we have demonstrated that binding of Pex5p to Pex14p is enhanced when Pex5p is loaded with a PTS1-containing peptide. In contrast, Pex5p binding to Pex13p, which involves only the SH3 domain, occurs at 20 -40-fold lower levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 34 publications
6
118
0
Order By: Relevance
“…Pex13p was not detectable in Mut34, Mut24, Mut123, Mut234, Mut124, Mut134, and Mut1234 (lanes 9 and 12 to 17). These results strongly suggested that WXXXF/Y motifs 2 to 4 of the minimal Pex13p-binding segment of Pex5p were essential for binding activity, consistent with recent observations for two yeast species (4,5,45), such as observations of residues W 100 to E 213 of P. pastoris Pex5p. Thus, it is most likely that mammalian Pex5p interacts with the N-terminal part, not with the C-terminal SH3 domain, of Pex13p via WXXXF/Y motifs 2 to 4.…”
Section: Vol 22 2002 Peroxisome Targeting Signal 1 Receptor Pex5p 1645supporting
confidence: 78%
See 1 more Smart Citation
“…Pex13p was not detectable in Mut34, Mut24, Mut123, Mut234, Mut124, Mut134, and Mut1234 (lanes 9 and 12 to 17). These results strongly suggested that WXXXF/Y motifs 2 to 4 of the minimal Pex13p-binding segment of Pex5p were essential for binding activity, consistent with recent observations for two yeast species (4,5,45), such as observations of residues W 100 to E 213 of P. pastoris Pex5p. Thus, it is most likely that mammalian Pex5p interacts with the N-terminal part, not with the C-terminal SH3 domain, of Pex13p via WXXXF/Y motifs 2 to 4.…”
Section: Vol 22 2002 Peroxisome Targeting Signal 1 Receptor Pex5p 1645supporting
confidence: 78%
“…Mammalian Pex5pL contains seven WXXXF/Y motifs, while two and three motifs are identified in Pex5p from S. cerevisiae and Pichia pastoris, respectively. The N-terminal part of P. pastoris Pex5p has recently been shown to be required for interaction with the Src homology 3 (SH3) domain of Pex13p (45). In S. cerevisiae, the pentapeptide motifs have been demonstrated to be involved in the interaction of Pex5p with Pex13p (5).…”
mentioning
confidence: 99%
“…This regards the inhibitory effect of anti-Pex13p antibodies on the peroxisomal import step of Pex5p. Pex13p is an intrinsic membrane component of the peroxisomal membrane probably involved in the recycling step of Pex5p back to the cytosolic compartment (45,49). In vitro binding assays and yeast and bacterial two-hybrid experiments have shown that this peroxin is capable of interacting directly with Pex14p and Pex5p (50).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, GST (glutathione transferase)-PEX13 pull-down assays have shown that the N-terminal 100 amino acids provide a binding domain for PEX5 (Otera et al, 2002), whereas in yeast, pull-down and two-hybrid assays have shown that the C-terminal SH3 (Src homology 3) domain provides a binding site for Pex5p (Bottger et al, 2000;Urquhart et al, 2000). A. thaliana PEX7 also bind the N-terminus of PEX13 in a yeast two-hybrid assay (Mano et al, 2006).…”
Section: Docking Complexmentioning
confidence: 99%
“…Pex13p can bind directly to Pex7p in S. cerevisiae (Girzalsky et al, 1999) and A. thaliana (Mano et al, 2006). There is a general lack of both quantitative and kinetic data; however, Urquhart et al (2000) used overlay-binding assays to demonstrate that cargo-loaded P. pastoris Pex5p binds more efficiently to Pex14p, whereas empty Pex5p binds more efficiently to Pex13p. The different affinities of these two peroxins for cargo-loaded or unloaded Pex5p suggests docking of Pex5p at Pex14p, then handover to Pex13p for release of the PTS1 cargo.…”
Section: Stoichiometry Affinity and Order Of Binding Interactions Ammentioning
confidence: 99%